Operasi dan Pemeliharaan (O&P) Irigasi Masa Depan Sebuah Gagasan Mengantisipasi Perubahan Kebijakan dan Lingkungan - Sigit Supadmo Arif (agriTECH, 2006)
During some later years, several calamities had occured several times in the country. Landslides and floos come during wet season and in the opposite drought happened in dry season. Just wet season end, drought comes and threat all activities of human life in most region in the country. In some places all of there conditions change very quickly. Mostly, all those occured due to inappropriate management of water resources. This paper aims at discussing some prospects of water resources research in the future. One knows that the existence of water resources in the earth is a complex system and satisfies some certain natural laws to form an natural equilibrium, so, it more easilt if management of water resources research is approached by applying system analysis. The paper also discussed application of new paradigm as well as several new research methods in social, economical and engineering aspects in water resources management.